Income, wealth and economic inequality in Australia - Tapper, Alan; Fenna, Alan (Australian Social Policy Association, 2018)
Economic well-being and economic inequality are usually quantified using income measurements of various sorts. Such analyses overlook the contribution of wealth – a potentially very significant factor. In this article, we integrate wealth and income data to provide a more comprehensive accounting of economic well-being and economic inequality in Australia. Using the Australian Bureau of Statistics Household Expenditure Survey microdata for 2009–2010, we present a cross-sectional analysis of wealth-adjusted income. We examine the relative contributions of income-and-wealth to wealth-adjusted income and compare the distribution of wealth-adjusted income to the distribution of income and the distribution of wealth. Wealth, we find, makes up between one-fifth and two-fifths of wealth-adjusted income; the incorporation of wealth increases the inequality already present in the income distribution (as measured using final incomes) by about 25 per cent.